Juridical Review of Non-Litigation Medical Dispute Resolution Between Patients, Doctors and Hospitals in Konawe Regency - Ma’ruf Akib; Edward Kurnia Limijadi; Ign. Hartyo Purwanto (Universitas Katolik Soegijapranata Semarang, 2022)
Abstract: The relationship between doctors and patients is a form of social relationship in which the relationship experiences dynamics. The dynamics that occur can create a harmonious atmosphere between the two parties. Bad relationships can also occur when one party feels aggrieved by the impact of the relationship. Bad relationships occur because patients feel dissatisfied with the health services they receive. Disputes between patients and doctors can be caused by problems of professional ethics or violations of health laws. Doctors' actions that are not by the code of ethics have the potential to be disputed. The purpose of this study is to identify and analyze non-litigation medical dispute resolution between patients, doctors, and the Konawe district general hospital. This study uses a sociological juridical approach with descriptive-analytical research specifications. The type of data used is primary data and secondary data. The data collection methods consist of 1. Literature study; 2. Field Study. The data analysis method used is qualitative. The results of the discussion can be seen that the implementation of Non-Litigation Medical Dispute Resolution between Patients, Doctors, and Hospitals is not by the aspects of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution while the consultation between patients and the Konawe Hospital cannot be categorized as mediation because it is not facilitated by an official mediator so that it is not by Article 29 of Law Number 36 of 2009 concerning Health.Keywords: settlement, medical dispute, non-litigation, patient, doctor; hospital Abstrak: Hubungan antara dokter dan pasien merupakan salah satu bentuk hubungan sosial dimana dalam hubungan itu mengalami dinamika. Dinamika yang terjadi dapat menimbulkan suasana yang harmonis antara dua pihak. Hubungan yang buruk juga dapat terjadi ketika salah satu pihak merasa dirugikan atas dampak hubungan yang terjadi. Hubungan yang buruk terjadi karena pasien merasa tidak puas atas pelayanan kesehatan yang diterima. Sengketa antara pasien dan dokter dapat disebabkan masalah etika profesi atau pelanggaran hukum kesehatan. Tindakan dokter yang tidak sesuai kode etik berpotensi sengketa. Tujuan penelitian ini yaitu: untuk mengetahui dan menganalisis penyelesaian sengketa medis non litigasi antara pasien, dokter dan rumah sakit umum daerah kabupaten Konawe. Penelitian ini memakai pendekatan pendekatan yuridis sosiologis dengan spesifikasi penelitian deskriptif analitis. Jenis data yang digunakan adalah Data Primer dan Data sekunder. Adapun metode Pengumpulan data terdiri dari: 1. Studi Kepustakaan; 2. Studi Lapangan. Metode analisis data yang digunakan adalah metode analisis kualitatif. Hasil pembahasan dapat diketahui bahwa pelaksanaan Penyelesaian Sengketa Medis Non Litigasi antara Pasien, Dokter dan Rumah Sakit tidak sesuai dengan aspek Undang Undang Nomor 30 Tahun 1999 tentang Arbitrase dan Alternatif Penyelesaian Sengketa sedangkan musyawarah antara pasien dengan pihak RSUD Konawe belum dapat dikategorikan sebagai mediasi karena tidak difasilitasi oleh seorang mediator resmi sehingga tidak sesuai dengan Pasal 29 Undang-Undang Nomor 36 Tahun 2009 tentang Kesehatan.Kata Kunci: penyelesaian, sengketa medis, non litigasi, pasien, dokter; rumah sakit